Penyuluhan Pembuatan Disinfectant kepada Karyawan Laundry di Condongcatur Yogyakarta - Bagus Wahyu Utomo (Universitas Islam Indonesia, 2021)
Various attempts have been made to combine in one composition to kill bacteria and detergents. So antiseptics such as coal tar, phenolic and crystalline preparations, mercury salts, as compounds of chlorides and iodides, arsenic and silver, and essential oils such as resin oil, terpenes, almond oil, and thyme oil. Has been used with soap, with alkaline salts of Long-chain fatty acids. The effective disinfectant is determined based on several parameters, namely: the phenol coefficient of the disinfectant and the water quality results measured from pH, dissolved oxygen (DO, dissolved oxygen), temperature and disinfectant cost.The antimicrobial effectiveness of the four selected disinfectants (Dettol, Izal, Z-Germicide and Jik) was determined using the agar diffusion method (disc paper). The results show that Dettol is most effective against the test organisms compared to other disinfectants. All noted the least antimicrobial activity. The phenol coefficient value also shows that Dettol is better when compared to other tested disinfectants. Disinfectant for external use is required to avoid infection or related disease caused by this test microorganism.This counselling was successful even though it encountered several obstacles during implementation. The steps that need to be done in making a disinfectant are determining the ingredients that are safest for humans but effective in eliminating various types of bacteria and viruses. The second stage is the implementation of activities. Activities carried out jointly by employees according to what has been planned. In the third stage, monitoring and evaluation of activities are carried out. This process is also carried out jointly with employees. Employees who work directly to random consumers will really need special knowledge on how to make disinfectant fluids. Keywords: Antiseptic, Disinfectant, Virus